FLASH FICTION DI INDONESIA: 1858 HINGGA KINI - Ibnu Wahyudi (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
Flash fiction or what is better known in Indonesia as "mini fiction" or also "mini prose" is not a form of work that arises as a result of dealing with limited space today but also has something to do with the level of literacy at a certain time. It is not surprising that the publication of early prose in Indonesia, which at that time was still under colonial rule, namely in the mid-19th century, was essentially similar to the “fiksi mini” that has been developing in Indonesia in recent years. Thus, this paper is an attempt to straighten out and trace the dynamics of the flash fictions which have been published in Indonesia since more than a century ago. Because of this tracking will, reading of the flash fictions that have been published is a must. From the data obtained, several “fiksi mini” were used which were clearly able to confirm the existence of flash fictions which could be said to have been ahead of its time. Facts like this are results that are worth caring about considering that the present atmosphere has existed in the past. This kind of literary reality reaffirms the understanding that literary works in particular, whatever their form, have the power to enter the future unconsciously or not on purpose. In form, what happens is the tacit proclamation of a genre, for example, while in content it is usually concerned with some sort of natural forecast or prediction.